Medication-assisted treatment for substance use disorders within a national community health center research network. Issue 4 (1st October 2016) - Rieckmann, Traci; Muench, John; McBurnie, Mary Ann; Leo, Michael C.; Crawford, Phillip; Ford, Daren; Stubbs, Jennifer; O'Cleirigh, Conall; Mayer, Kenneth H.; Fiscella, Kevin; Wright, Nicole; Doe-Simkins, Maya; et al.
ABSTRACT: Background: The Affordable Care Act increases access to treatment services for people who suffer from substance use disorders (SUDs), including alcohol use disorders (AUDs) and opioid use disorders (OUDs). This increased access to treatment has broad implications for delivering health services and creates a dramatic need for transformation in clinical care, service lines, and collaborative care models. Medication-assisted treatments (MAT) are effective for helping SUD patients reach better outcomes. This article uses electronic health record (EHR) data to examine the prevalence of EHR-documented SUDs, patient characteristics, and patterns of MAT prescribing and screening for patients within the Community Health Applied Research Network (CHARN), a national network of 17 community health centers that facilitates patient-centered outcomes research among underserved populations. Methods: Hierarchical generalized linear models examined patient characteristics, SUD occurrence rates, MAT prescription, and human immunodeficiency virus (HIV) and hepatitis virus C screening for patients with AUDs or OUDs. Results: Among 572, 582 CHARN adult patients, 16, 947 (3.0%) had a documented AUD diagnosis and 6, 080 (1.1%) an OUD diagnosis. Alcohol MAT prescriptions were documented for 547 AUD patients (3.2%) and opioid MAT for 1, 764 OUD patients (29.0%). Among OUD patients, opioid MAT was significantly associated with HIV screening (odds ratio [OR] = 1.31, P < .001) in OUD patients, as was alcohol MAT among AUD patients (OR = 1.30, P = .013). Conclusions: These findings suggest that effective opioid and alcohol MAT may be substantially underprescribed among safety-net patients identified as having OUDs or AUDs.